The Role Of Educational Environment In Academic Stress: The Mediating Effects Of Self-Efficacy And Social Support Among University Students - Kurnia Khafidhatur Rafiah; Sulwani Husna Afrizal (International Journal of Management and Business Economics, 2026)
This study examines the role of the educational environment in academic stress among university students, focusing on the mediating effects of self-efficacy and social support. A total of 106 undergraduate students from universities in Indonesia participated in an online survey measuring educational environment, self-efficacy, social support, and academic stress. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the educational environment has a significant positive effect on self-efficacy (β = 0.640, p < .001) and social support (β = 0.590, p < .001) but does not directly reduce academic stress (β = −0.095, p = .24). Self-efficacy has a significant negative effect on academic stress (β = −0.219, p = .002), whereas social support does not show a significant effect (β = 0.045, p = .494). The indirect effect of the educational environment on academic stress through self-efficacy is significant (β = −0.141, p = .019), while the indirect path through social support is not. The model explains a small portion of the variance in academic stress (Adjusted R² = 0.041; Q² = 0.027), indicating the presence of other relevant stressors beyond the educational environment. These findings highlight the importance of fostering self-efficacy within supportive educational environments to help students cope with academic stress.